2010
DOI: 10.1038/cr.2010.89
|View full text |Cite
|
Sign up to set email alerts
|

Pericentrin contains five NESs and an NLS essential for its nucleocytoplasmic trafficking during the cell cycle

Abstract: Pericentrin, a conserved centrosomal component, provides the structural scaffold to anchor numerous centrosomal proteins, and thus plays an essential role in the organization and function of the centrosome and the mitotic spindle. Although pericentrin was shown to localize in the cytoplasm and reported to be sensitive to leptomycin B (LMB), a specific inhibitor of Crm1, the regions within pericentrin that serve as signals for transporting in and out of the nucleus have not yet been identified. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…32, 33 Besides, immunoprecipitation showed that Calu-15 also interacted with Ran GTPase (Figure 2d), which has been reported to disassociate the importin–cargo complex and be required for the nuclear import process. 33, 34 Moreover, the cotransfection with RanQ69L, which is a mutant defective in GTPase activity, 35 largely inhibited the nuclear localization of Calu-15 (Figure 2e). Therefore, the nuclear import process of Calu-15 is mediated by importin- α and regulated by Ran GTPase.…”
Section: Resultsmentioning
confidence: 95%
“…32, 33 Besides, immunoprecipitation showed that Calu-15 also interacted with Ran GTPase (Figure 2d), which has been reported to disassociate the importin–cargo complex and be required for the nuclear import process. 33, 34 Moreover, the cotransfection with RanQ69L, which is a mutant defective in GTPase activity, 35 largely inhibited the nuclear localization of Calu-15 (Figure 2e). Therefore, the nuclear import process of Calu-15 is mediated by importin- α and regulated by Ran GTPase.…”
Section: Resultsmentioning
confidence: 95%
“…As examples, both the ciliary axoneme-associated radial spoke protein 3 (RSPH3–OMIM: 615876) [100] and the pericentriolar and ciliary basal body-associated protein pericentrin (PCNT: OMIM: 605925) [51] have been found to contain functional nuclear localization (NLS) and nuclear exclusion (NES) sequences. Similarly parafusin, a signaling scaffolding protein, has been found localized to the base of primary cilia in a variety of mammalian cell types and within the nuclei of fibroblasts [77].…”
Section: Implications Of the Evolutionary Origin Of Ciliamentioning
confidence: 99%
“…The small GTPase Ran regulates NE and NPC assembly, as well as nucleocytoplasmic transport and mitotic spindle formation [10,[14][15][16][17][18][19][20][21]. Chromatin-independent NE assembly can be induced using artificial beads coated with Ran in the extracts from Xenopus eggs or somatic…”
Section: Introductionmentioning
confidence: 99%